The Role of Pseudomonas aeruginosa in the Pathogenesis of Corneal Ulcer, Its Associated Virulence Factors, and Suggested Novel Treatment Approaches - Lorina Badger-Emeka; Promise Emeka; Krishnaraj Thirugnanasambantham; Abdulaziz S. Alatawi (MDPI AG, 2024)
Background: Pseudomonas aeruginosa (P. aeruginosa), is a diverse Gram-negative pathogen commonly associated with a wide spectrum of infections. It is indicated to be the most prevalent causative agent in the development of bacterial keratitis linked with the use of contact lens. Corneal infections attributed to P. aeruginosa frequently have poor clinical outcomes necessitating lengthy and costly therapies. Therefore, this review looks at the aetiology of P. aeruginosa bacterial keratitis as well as the bacterial drivers of its virulence and the potential therapeutics on the horizon. Method: A literature review with the articles used for the review searched for and retrieved from PubMed, Scopus, and Google Scholar (date last accessed 1 April 2024). The keywords used for the search criteria were "Pseudomonas and keratitis, biofilm and cornea as well as P. aeruginosa". Results: P. aeruginosa is implicated in the pathogenesis of bacterial keratitis associated with contact lens usage. To reduce the potential seriousness of these infections, a variety of contact lens-cleaning options are available. However, continuous exposure to a range of antibiotics doses, from sub-inhibitory to inhibitory, has been shown to lead to the development of resistance to both antibiotics and disinfectant. Generally, there is a global public health concern regarding the rise of difficult-to-treat infections, particularly in the case of P. aeruginosa virulence in ocular infections. This study of the basic pathogenesis of a prevalent P. aeruginosa strain is therefore implicated in keratitis. To this effect, anti-virulence methods and phage therapy are being researched and developed in response to increasing antibiotic resistance. Conclusion: This review has shown P. aeruginosa to be a significant cause of bacterial keratitis, particularly among users of contact lens. It also revealed treatment options, their advantages, and their drawbacks, including prospective candidates.